DETERMINANTS OF GREEN PURCHASE INTENTION AMONG BEAUTY PRODUCT CONSUMERS IN BATAM CITY - Florence Aletta Manalu; Reni Shinta Dewi; Hari Susanta Nugraha (Jurnal Ekonomi, 2023)
The significant development of the cosmetic industry, particularly in Indonesia, is facing various challenges and issues. Apart from the problem of packaging quality that does not meet environmental standards, there are still cosmetic products found to contain harmful chemicals (such as mercury, banned colorants, carcinogens, and microbial contaminants) that can negatively impact the health of users. The environmental issues and negative effects of cosmetic products on consumers indicate that there are still cosmetic manufacturers or distributors who have not been able to implement the Triple Bottom Line principle, consisting of People, Planet, and Profit (3P's). These companies focus solely on maximizing profits while disregarding the impact of products containing harmful chemicals on public health (people) and continue to use environmentally unfriendly raw materials and packaging (planet). This study aims to examine the direct and indirect effects of green brand image and LOHAS on Green Purchase Intention, either through green attitude. The study gathered 200 respondents as the sample. The research utilized the SEM analysis method using the Smart PLS 3.3.3 statistical tool. The results of partial significance testing found that Green Brand Image can influence Green Attitude and Green Purchase Intention. Meanwhile, LOHAS only has a direct influence on Green Attitude. The mediating test results found that Green Attitude can mediate the influence of Green Brand Image and LOHAS on Green Purchase Intention.